Translation, validity, and reliability of NUTRISCORE: the nutrition risk assessment screening test for Turkish cancer patients - ATASOY, BESTE MELEK; YUMUK, PERRAN FULDEN (WILEY, 2022)
Purpose The aim was to determine the validity and the reliability of the Turkish version of the screening test named NUTRISCORE in cancer patients. Methods The language validity of the Turkish form of the study scale was provided by the translationback-translation method. NUTRISCORE and nutritional risk screening (NRS)-2002, malnutrition screening tool (MST), and European Diagnostic Criteria (EDC) were administered to 240 volunteers in oncology clinics, and receiver operating characteristic curves (ROC) were calculated for the validity and reliability analysis. Cohen's kappa coefficient was used to determine the fit between the screening tests. Results Thirteen experts were consulted for scale content validity, and the content validity index was found to be 0.94. The scale was administered to 67 patients with 4-week intervals for test-retest reliability, and a positive, high-level and statistically significant relationship was found between the two measurements (r = 0.971, P < 0.01). Compared with the reference test NRS-2002, the specificity values of NUTRISCORE, MST, and EDC screening tests were found to be 100%, 83%, and 91%, whereas the sensitivity values of same screening tests were calculated as 85%, 91% and 81%, respectively. According to Cohen's kappa statistics, the kappa agreement between NRS-2002 and NUTRISCORE was 0.88, the kappa agreement between NRS-2002 and MST was 0.34, and it was found to be 0.73 for NRS-2002 and EDC. Conclusion The nutrition screening test named NUTRISCORE showed adequate validity and reliability in Turkish and can detect malnutrition risk of cancer patients treated in oncology clinics as a screening tool.
Keywords: malnutrition; nutrition assessment; nutrition screening; reliability; validity; HOSPITAL MALNUTRITION; WEIGHT-LOSS; TOOL; CHEMORADIOTHERAPY; RECOMMENDATIONS; CHEMOTHERAPY; PREVALENCE; INPATIENTS